Exploring academic identities of EFL novice writers - Juliaty, Hanna (Universitas Pendidikan Indonesia, 2019)
In academic writing, undergraduate EFL learners are not required only to apply correct L2 writing system, but more profoundly, construct and convey ideas in ways recognised in their discipline as they continuously create and recreate identities as members of their academic community. Such a process of identity construction shapes EFL novice writersâ€™ characteristics and nurture their growth as writers in the academic environment. This study, thus, aims to explore the portrayal of academic identities of undergraduate EFL novice writers. Eight Indonesian undergraduate students of an English Department in a private Indonesian university participated in this study. The data collected included an autobiography journal, a semi-structured interview and two essay assignments. The data were analysed qualitatively by employing IvaniÄâ€™s (1998) concept of writer identity, consisting of autobiographical self, discoursal self and authorial self, and Hylandâ€™s (2010) metadiscourse model. The findings reveal that despite numerous writing repertoires applied to display aspects of autobiographical, discoursal and authorial selves in the learnersâ€™ academic writing, the portrayal of academic identities in the writing is overall weak due to the struggles that the learners faced in adjusting and engaging themselves in the academic community of their discipline. Some recommendations in relation to L2 academic writing practice for EFL undergraduate students include facilitating students to have more exposure and access into L2 academic writing culture and academic community of their discipline.